Méthodes de gestion des graines dans les banques de gènes - International Plant Genetic Resources Institute (1995)
Published in collaboration with Technical Centre for Agricultural and Rural Co-operation (CTA). This the french version of Procedures for Handling Seeds in Genebanks.